Mathematical problems of thermomechanics for deformable bodies under thermal irradiation - Hachkevych , O. R.; Kushnir , R. M.; Terletskii , R. F. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 535.51, 535.55, 539.3It is a review of the results of researches in the field of mathematical problems of the thermomechanics of magnetizable and polarizable electroconductive deformable bodies under electromagnetic irradiation, which are carried out at Ya. S. Pidstryhach Institute for Applied Problems of Mechanics and Mathematics, NAS of Ukraine. In this paper, we formulate the problems of mathematical physics that describe the thermal and thermal stress state in such bodies taking into account the peculiarities of electromagnetic action in different frequency ranges and analyze the methods of study of the thermomechanical behavior of bodies (in particular, of different transparency, as semitransparent as well as opaque) in these ranges under thermal irradiation.